Metode Smoothed Particle Hydrodynamicsuntuk Aliran Laminar Tak Kompresibel Dengan Masukan Dan Keluaran Di Saluran Terbuka - Burniadi Moballa (Techno Bahari, 2017)
Smoothed Particle Hydrodynamics (SPH) is a meshfree and Lagrangian numerical method. SPH is especially suitable for simulation of free surface flow problems. When used to simulate an incompressible fluid, SPH employs a weakly compressbile model (WCSPH). In the weakly compressible SPH (WCSPH), the density of the fluid is allowed to vary slightly and the pressure is obtained by employing an equation of state. However, the application of SPH to the fluid-solid interaction problem close to a free surface is relatively few. There are two main problems that stand in the way. First, the pressure field predicted by the WCSPH model is plagued by numerical noise. Second, there is no established scheme to implement inlet and outlet boundaries. Basically, inlet and outlet are Eulerian boundaries. Therefore, a treatment for the particles that move beyond the outlet and a method for supplying particles at the inlet are required. Hence, this work attempts to address these problems by developing methods to predict the pressure field with sufficient accuracy and to implement inlet and outlet boundaries. We developed an incompressible SPH (ISPH) method based on the iterative correction method to obtain more accurate pressure field. We adopted the velocity interpolation method proposed by Rhie and Chow to the current ISPH method to treat the pressure checkerboarding problem. Inlet and outlet boundaries are implemented by dragging the particles that moved beyond the outlet back to the inlet. The developed ISPH methodis applied to study flow past circular cylinder between parallel walls andflow past circular cylinder beneath a free surface.